1994
DOI: 10.1007/bf01553326
|View full text |Cite
|
Sign up to set email alerts
|

Localization of uridine monophosphate synthase (UMPS) gene to river buffalo chromosomes by FISH

Abstract: Uridine monophosphate synthase plays an important role in pyrimidine synthesis, converting orotic acid to uridine 5' monophosphate. In cattle, UMPS deficiency is inherited as a monogenic autosomal recessive trait. While heterozygous carriers are phenotypically normal, homozygotes are lethal in utero (Shanks et al. 1992). UMPS has been mapped to human chromosome 3q13 (Qumsiyeh et al. 1989), sheep chromosome 1q (Burkin et al. 1993) and cattle chromosome 1q31 (Ryan et al. 1994). In the present study we used a cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Cytological studies of buffalo chromosome one (BBU1) indicated that BBU1 q is homologous to BTA 1 (I annuzzi et al 1990). This was confirmed by the assignment of UMPS to buffalo BBU1q (I annuzzi et al 1994) which has been previously assigned to cattle U10 BTA 1 (R yan et al 1994). However, regarding the small acrocentric chromosome presenting the short arm there is still some controversy.…”
Section: Resultssupporting
confidence: 71%
“…Cytological studies of buffalo chromosome one (BBU1) indicated that BBU1 q is homologous to BTA 1 (I annuzzi et al 1990). This was confirmed by the assignment of UMPS to buffalo BBU1q (I annuzzi et al 1994) which has been previously assigned to cattle U10 BTA 1 (R yan et al 1994). However, regarding the small acrocentric chromosome presenting the short arm there is still some controversy.…”
Section: Resultssupporting
confidence: 71%
“…The major histocompatibility complex (MHC) was assigned to BTA 23 (F ries et al 1991; H ediger et al 1991; I annuzzi et al 1993a) and BBU 2p (I annuzzi et al 1993a). UMPS gene was first localized on BTA 1q31 (R yan et al 1994) and then on BBU 1q13 (I annuzzi et al 1994).…”
Section: Resultsmentioning
confidence: 99%
“…It is then speculated that the investigated syntenic groups can be assigned to buffalo chromosomes BBU 10, BBU 1q, BBU 14, BBU 9, and BBU 15, respectively. The gene for UMPS (U10) has already been assigned to BBU 1q, using in situ hybridization (I annuzzi et al 1994).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation